(untitled) (Modern education and development, 2025)
Every person in society does not live alone, outside. He grows up among people, grows up, lives, communicates with many people of various categories throughout his life and work. This arises from the need to satisfy the daily needs of a person. Therefore, he always behaves ethically and aesthetically. Therefore, our nurses must also treat patients with a humane attitude and adhere to the principles of ethics and aesthetics.